Ayurveda Management of KAMPA VATA ( PARKINSONISM) - Acharya, Shripathi; Acharya, Rajeshwari S (International Research Journal of Ayurveda & Yoga, 2020)
Degenerative disorders are common in Indian population. Parkinsonism is a degenerative disorder of nervous system. It usually occurs in middle and old age. Akinesia, rigidity, tremors, masked and expressionless facies and Cesar gait are usually seen clinical features in Parkinsonism. The clinical features which can correlated with this disease in Ayurveda is Kampavata , a vataja nanatmaja vyadhi. According to modern sciences, there will be depletion of adrenergic neurotransmitter, dopamine in presynaptic neural endings in areas like thalamus, limbic system, substansia nigra and reticular activating system. This causes generalized symptoms like akinesia, rigidity and tremors. In US, nearly 50,000 people are diagnosed each year and half million people are living with this condition. Certain Ayurveda medicines are found useful in parkinsonism. Kapikacchu choorna , lohabhraka sindoora, vajrabhraka sindoora, siddha makaradhwaja, hemagarbha pottali, vanari kalpa, are some medications which give good resultsin the management of parkinsonism . The present paper highlights the role of Ayurvedic medicine in the management of parkinsonism. vis a vis Kampavata.